Finite Element Assessment of Short Stem in Hip Arthroplasty Based on Different Activities - Haslina Abdullah; Norfazillah Talib; Mohd Nasrull Abdol Rahman; Mohamad Shukri Zakaria (International Journal of Integrated Engineering, 2025)
Stress shielding is a phenomenon that occurs when an implant absorbs too much of the load that would typically be distributed to the surrounding bone, resulting in reduced mechanical stimulation of the bone. In hip arthroplasty, the implant's design plays a crucial part in stress distribution at the interface of the implant and the adjacent bone. This study examines the stress distribution in hip arthroplasty implants using Finite Element Analysis (FEM), comparing conventional stems with short stems. Titanium alloy has been chosen as the material of the implant. Stress analysis has been conducted under five different activities: normal walking, walking upstairs, walking downstairs, standing, and sitting to study the effect of these activities on various lengths of stem. The results show that in the conventional stem, the highest stress concentrations occur at the joint and the tip of the implant, leading to stress shielding in the proximal area of the femur bone, which may result in bone resorption and potential implant complications over time. On the contrary, the short stem exhibits higher stress values at the neck of the implant for all activities. However, the short stem demonstrates a uniform stress distribution pattern compared to the conventional stem. In addition, the analysis found that conventional stem practices had higher stress levels throughout all activities than the short stem practices. Among the activities examined, walking activities generated the highest stress, followed by activities such as upstairs walking, normal walking, standing, and sitting. These findings provide insight into the mechanical performance of hip implants and suggest that short stems offer advantages in reducing stress shielding and enhancing longevity.